TEMA PUISI INDONESIA MODERN PERIODE AWAL - Mahmud, Amir (Balai Bahasa Jawa Timur, 2011)
Dunia puisi Indonesia modern terus mengalami perkembangan yang cukup baik sejak tahun 1800-an melalui terbitan majalah-majalah, seperti Bianglala (1870), Tjahaja Siang (1896), atau Pandji Poestaka (1923). Media seperti itu memunculkan nama-nama besar penyair Indonesia, seperti Or. Mandank, Sanusi Pane, dan Amir Hamzah. Perkembangan itu telah me- munculkan berbagai pemikiran generasi muda untuk meneliti dan menginventarisasikannya. Sampai saat ini banyak yang melakukan penelitian terhadap puisi Indonesia modern dari segi struktur, estetika, atau makna. Secara tidak langsung penelitian itu akan bersentuhan dengan masalah budaya dan penyairnya. Tidaklah lengkap kalau berbicara masalah perpuisian di Indonesia tanpa melibatkan penyair, sosial, dan budayanya. Namun, tulisan ini tidak melibatkan penyair, sosial, dan budayanya secara khusus, kajian ini hanya terfokus pada aspek tema, seperti tema cita-cita merdeka, keagamaan, kesatuan, nasihat, alam lingkungan, atau kritik sosial. Abstract: The world of modern Indonesian poetry has continued to have a fairly good development since the year of the 1800s via magazine publications such as Bianglala (1870), Tjahja Siang (1986), or Pandji Poestaka (1923). Such medias had brought out great Indonesian poets like Or. Mandank, Sanusi Pane, and Amir Hamzah. The development has raised various ideas of the young generation to study and inventory them. Until now, there have been many studies on modern Indonesian poetry from the aspect of structure, aesthetic, and meaning. Indirectly, the studies would be involved with cultural issues and the poets. It is incomplete to discuss the Indonesian poetry issues without involving the poets and their social and culture in particular. Nevertheless, this study does not involve the poets and their social and culture in particular. Instead, this study focuses on the aspect of the theme, such as the theme of desire for independence, religion, unity, advice, environment, or social critic. Key Words: poetry; theme; poet; mass media; native; and Netherlands East Indies